An Extract out of Josephus's Discourse to The Greeks Concerning Hades - Josephus, Flavius, 38?-100?; Whiston, William, 1667-1752 (Salt Lake City, UT : Project Gutenberg, 2001)
"An Extract out of Josephus's Discourse to The Greeks Concerning Hades" by Flavius Josephus is a historical and theological discourse written in the early centuries of the Common Era. This work discusses the nature of Hades, the afterlife, and the fates of souls based on their earthly lives. Josephus, a first-century Jewish historian, aims to clarify these concepts to a Greek audience, addressing their philosophical ideas about the soul and the afterlife. In this extract, Josephus elaborates on Hades as a place for the souls of both the righteous and the unrighteous, describing it as a subterranean region of darkness and confinement. He contrasts the experiences of the just, who are led to a place of light and joy called "The Bosom of Abraham," with the unjust, who face punishment and despair. Josephus emphasizes the belief in the resurrection of the body, arguing against Greek philosophical notions of the immortality of the soul without bodily resurrection. Ultimately, he asserts that all will face divine judgment, leading to eternal reward for the just and eternal punishment for the unjust, while encouraging the Greeks to embrace faith in God to share in the promised eternal happiness. (This is an automatically generated summary.)
Release date is 2001-10-01
Produced by David Reed, and David Widger
Keywords: Jews -- History; Jews -- Antiquities